ANALISIS PENGARUH STRUKTUR MODAL, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP NILAI PERUSAHAAN (Studi Empiris Terhadap Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia (BEI)) - Ade Imamul Muwachidin, 10.05.52.0082; Maryono, Maryono (Students Journal of Accounting and Banking, 2014)
The Company has long-term goal is to maximize shareholder wealth. Maximizing shareholder wealth can be reached by maximizing the present value. The purpose of this study was to determine the effect of capital structure, profitability and firm size on the value of the company in Indonesia Stock Exchange 2010-2012. This study population is listed manufacturing industry in Indonesia Stock Exchange in 2010-2012. Sampling method with purposive sampling method, with some predetermined criteria, the number of samples is 74 manufacturing companies. The research data is secondary data obtained from the Indonesian Capital Market Directory (ICMD) 2010-2012. Data analysis techniques used in this study is multiple linear regression analysis. The results showed that: 1) capital structure, Profitability and has unsignificant negative effect on firm value, 2) firm size has significant positive effect on firm value.Keywords: capital structure, profitability, firm size, firm value